Identificación y caracterización botánica de plantas mucilaginosas de los andes ecuatorianos en Cotopaxi e Imbabura. - Arguero Jácome, Brayan Francisco (2020)
This research was carried out with the purpose of identifying and characterizing mucilaginous plants to potentiate their application and implementation in the food field. The limited botanical information on Ecuadorian plants with mucilage encouraged us to do this study. Putzalahua hill (Cotopaxi) and Miguel Egas Cabezas, Peguche (Imbabura) were taken as a representative study site for collecting the botanical specimens. The investigation details the materials, methods, techniques and instruments that help the collection and botanical characterization of plants with the presence of mucilage. In each locality, a transect was established respectively; and aan extrusion test was carried out on the plants for later collection. These plants were transferred to the UTCEC herbarium to confirm the presence of mucilage with distilled water, only plant stems and leaves were tested. A total of 20 species tested positive for mucilage and 80 duplicates were collected and transferred to the UTCEC herbarium to be botanically described and sent to herbaria from Ecuador and the world. In the Putzalahua Hill, 6 botanical families with 10 species, and in Peguche 8 botanical families with 10 species were identified. Asteraceae, Fabaceae, Malvaceae, Pteridophyta were the families with higher concentration of mucilage. These are the first botanical data of wild species with mucilage from Ecuador. Fabaceae, Malvaceae, and Lamiaceae were families that previous studies had also found positive results for mucilages. On the other hand, this study records for the first time the presence of mucilage in the families Calceolariaceae, Commelinaceae, Polygalaceae, Cyperaceae, Amaranthaceae, Verbenaceae, and Solanaceae. The results from this research are a contribution to botany, and agroindustry, as mucilages can be used emulsifiers, thickeners and as clarifyiers.